A complex picture of associations between two host mussels and symbiotic bacteria in the Northeast Atlantic - Rodrigues, CF (2013)
Among chemosymbiotic metazoans found at deep-sea hydrothermal vents, cold seeps and organic falls, members of the mussel clade Bathymodiolinae (Bivalvia: Mytilidae) have evolved interactions with a higher diversity of bacterial lineages than other bivalve groups. Here, we characterized the bacteria associated with "Bathymodiolus" mauritanicus and Idas-like specimens from three sites in the Northeast Atlantic (two mud volcanoes in the Gulf of Cadiz and one seamount of the Gorringe Bank). Phylogenetic analysis of bacterial 16S rRNA-encoding gene sequences demonstrated that "B". mauritanicus has a dual symbiosis dominated by two phylotypes of methane-oxidising bacteria and a less abundant phylotype of a sulphur-oxidising bacterium. The latter was the dominant phylotype in a sympatric population of Idas-like mussels at the Darwin mud volcano. These results are the first report of a bacterial phylotype shared between two deep-sea mussels from divergent clades. This sulphur-oxidising bacterium was absent from Idas-like specimens from the other two sites (Gorringe Bank and MeknSs mud volcano), in which bacterial clone libraries were dominated by other Gammaproteobacteria related to symbionts previously identified in Idas modiolaeformis from the Eastern Mediterranean. All Idas-like specimens studied herein are closely related and also related to I. modiolaeformis. However, they probably display different associations with bacteria, with the possible absence of both methane- and sulphur-oxidising symbionts at the Gorringe Bank. These results draw a very complex picture of associations between mussels and bacteria in the Northeast Atlantic, which could be highly variable depending on locale characteristics of the habitats.